Sentimen Investor terhadap Stock Return JII di Awal COVID-19 - Istiqomah, Istiqomah; Wardhani, Dian Kusuma; Supratiwi, Wiwik; Ratnawati, Tri (E-Jurnal Akuntansi; Vol 31 No 5 (2021), 2021)
The research objective is to obtain empirical evidence of the negative influence of investor sentiment on the Jakarta Islamic Index stock return at the beginning of Covid-19. The research contributes to the Islamic finance literature and its supports agency theory, behaviour finance and signaling theory. The research sample used 30 companies listed in the Jakarta Islamic Index for the first semester of 2020. The final sample is 180 observational data. Fourth classical assumption uses, and result show passed all the classical assumption. This study uses control variables such as firm size and firm age. Multiple linear regression as an analysis processed with SPSS version 23. Research findings show a significant negative effect of investor sentiment on Jakarta Islamic Index stock returns at the beginning of Covid-19. This study implicates to management, shareholders and investor. Keywords: Investor Sentiment; Stock Return; COVID-19.